1996
DOI: 10.2307/3870236
|View full text |Cite
|
Sign up to set email alerts
|

Plant Cell Responses to Arbuscular Mycorrhizal Fungi: Getting to the Roots of the Symbiosis

Abstract: INTRODUCTIONSince their colonization of terrestrial ecosystems, plants have developed numerous strategies to cope with the diverse biotic and abiotic challenges that are a consequence of their sedentary life cycle. One of the most successful strategies is the ability of root systems to establish mutualistic and reciprocally beneficial symbiotic relationships with microorganisms. Mycorrhizas, the intricate associations roots form with specific fungal groups, are by far the most frequent of these and represent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 48 publications
2
77
0
4
Order By: Relevance
“…However, Frühling et al (39) have determined that a novel leghemoglobin gene is induced in broad bean mycorrhizal roots; its function there is unknown. Bonfante-Fasolo et al (40) have observed that hydroxyproline-rich glycoproteins are found at the interface between the fungus and its host, and Gianinazzi-Pearson (41) reported that ENOD12, which encodes another putative proline-rich protein, is expressed in mycorrhizal roots in cells containing arbuscules.…”
Section: Discussionmentioning
confidence: 99%
“…However, Frühling et al (39) have determined that a novel leghemoglobin gene is induced in broad bean mycorrhizal roots; its function there is unknown. Bonfante-Fasolo et al (40) have observed that hydroxyproline-rich glycoproteins are found at the interface between the fungus and its host, and Gianinazzi-Pearson (41) reported that ENOD12, which encodes another putative proline-rich protein, is expressed in mycorrhizal roots in cells containing arbuscules.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the mechanism, rapid sugar transport via the arbuscule does not seem feasible after the cross wall in the trunk hypha develops. Circumstantial evidence that arbuscules are not essential for sugar transport comes from the existence of mutants of Pisum sativum (myc -2 ) in which arbuscules are rudimentary, but the fungus is still capable of spreading intercellularly within the roots presumably at the expense of sugars from the plant (Gianinazzi- Pearson 1996).…”
Section: Sugar Transfermentioning
confidence: 99%
“…These species have the capacity to establish atmospheric dinitrogen fixing symbiose with soil bacteria collectively named rhizobia, and to form symbiotic root mycorrhizae with soil fungi, thus facilitating their uptake of phosphate, water and other soil nutrients [1,2]. However, genetic analysis of these processes remains difficult in the major crop legumes due to features such as tetraploidy, large genomes and/or the lack of efficient methods for transgenesis.…”
Section: Introductionmentioning
confidence: 99%